Load-bearing composite fracture-fixation devices with tailored fibre placement for toy-breed dogs - Moritz Niko; Liesmäki Oliver; Plyusnin Artem; Keränen Pauli; Kulkova Julia (Elsevier B.V., 2025)
Fibre reinforced composites are attractive materials for hard tissue reconstructions, due to the high strength and low flexural modulus. However, lack of contourability in the operation theatre inhibits their clinical applications.
The study presents a novel in situ contourable composite implant system for load-bearing conditions. The implant system consists of a thin bioresorbable shell with several cavities, much like bubble-wrap. The central cavity contains a semi-flexible glass fibre preform prepared using Tailored Fibre Placement method. The preform is either pre-impregnated with a light curable resin, or the resin is injected into the cavity during the surgical procedure, followed by light curing. The semi-flexible glass fibre preforms were also examined as separate devices, “miniplates”. Two types of miniplates were scrutinized, a simplified pilot design and a spatially refined, “optimized” design. The optimized miniplates were implemented as biostable and bioresorbable versions.
The feasibility of the in situ contourable composite implant system was demonstrated. The potential of Tailored Fibre Placement for the semi-flexible glass fibre preforms and miniplates was confirmed in a series of biomechanical tests. However, structural optimization is required. Antebrachial fractures in toy-breeds of dogs are exemplar veterinary applications of the devices; further applications in veterinary and human patients are foreseen.